Modeling, Simulation and Position Control of 3 Degree of Freedom Articulated Manipulator - Hossein Sadegh Lafmejani; Hassan Zarabadipour (IAES Indonesian Section, 2013)
In this paper, the modeling, simulation and control of 3 degree of freedom articulated robotic manipulator have been studied. First, we extracted kinematics and dynamics equations of the mentioned manipulator by using the Lagrange method. In order to validate the analytical model of the manipulator we compared the model simulated in the simulation environment of Matlab with the model was simulated with the SimMechanics toolbox. A sample path has been designed for analyzing the tracking subject. The system has been linearized with feedback linearization and then a PID controller was applied to track a reference trajectory. Finally, the control results have been compared with a nonlinear PID controller.